Low-Level Speech Recognition of Children with Hearing Aids - Wolfe, Jace; Duke, Mila; Miller, Sharon; Schafer, Erin; Jones, Christine; Rakita, Lori; Dunn, Andrea; Battles, Jarrod; Neumann, Sara; Manning, Jacy (Journal of the American Academy of Audiology, 2022)
Background For children with hearing loss, the primary goal of hearing aids is to provide improved access to the auditory environment within the limits of hearing aid technology and the child's auditory abilities. However, there are limited data examining aided speech recognition at very low (40 decibels A [dBA]) and low (50 dBA) presentation levels.Purpose Due to the paucity of studies exploring aided speech recognition at low presentation levels for children with hearing loss, the present study aimed to (1) compare aided speech recognition at different presentation levels between groups of children with “normal” hearing and hearing loss, (2) explore the effects of aided pure tone average and aided Speech Intelligibility Index (SII) on aided speech recognition at low presentation levels for children with hearing loss ranging in degree from mild to severe, and (3) evaluate the effect of increasing low-level gain on aided speech recognition of children with hearing loss.Research Design In phase 1 of this study, a two-group, repeated-measures design was used to evaluate differences in speech recognition. In phase 2 of this study, a single-group, repeated-measures design was used to evaluate the potential benefit of additional low-level hearing aid gain for low-level aided speech recognition of children with hearing loss.Study Sample The first phase of the study included 27 school-age children with mild to severe sensorineural hearing loss and 12 school-age children with “normal” hearing. The second phase included eight children with mild to moderate sensorineural hearing loss.Intervention Prior to the study, children with hearing loss were fitted binaurally with digital hearing aids. Children in the second phase were fitted binaurally with digital study hearing aids and completed a trial period with two different gain settings: (1) gain required to match hearing aid output to prescriptive targets (i.e., primary program), and (2) a 6-dB increase in overall gain for low-level inputs relative to the primary program. In both phases of this study, real-ear verification measures were completed to ensure the hearing aid output matched prescriptive targets.Data Collection and Analysis Phase 1 included monosyllabic word recognition and syllable-final plural recognition at three presentation levels (40, 50, and 60 dBA). Phase 2 compared speech recognition performance for the same test measures and presentation levels with two differing gain prescriptions.Conclusion In phase 1 of the study, aided speech recognition was significantly poorer in children with hearing loss at all presentation levels. Higher aided SII in the better ear (55 dB sound pressure level input) was associated with higher Consonant-Nucleus-Consonant word recognition at a 40 dBA presentation level. In phase 2, increasing the hearing aid gain for low-level inputs provided a significant improvement in syllable-final plural recognition at very low-level inputs and resulted in a nonsignificant trend toward better monosyllabic word recognition at very low presentation levels. Additional research is needed to document the speech recognition difficulties children with hearing aids may experience with low-level speech in the real world as well as the potential benefit or detriment of providing additional low-level hearing aid gain.
Keywords: hearing aids; speech recognition; aided thresholds